Binding of aroma compounds with soy protein isolate in aqueous model: Effect of preheat treatment of soy protein isolate. (30th August 2019) - Guo, Jun; He, Zhiyong; Wu, Shengfang; Zeng, Maomao; Chen, Jie
Highlights: Nature or 80 °C preheated soybean protein isolate (PSPI) has two class binding sites for hexyl acetate, heptyl acetate. Linalyl formate, linalyl acetate, geraniol and linalool bind on the hydrophobic surface of soybean protein isolate (SPI). PSPI leading the interaction between flavors (hexyl acetate, heptyl acetate) and protein weaker, and leading the interaction between flavors (linalyl formate, linalyl acetate, linalool, geraniol) and protein reinforced. The salting out effect was detected for myrcene and limonene in the soybean protein isolate aqueous. Abstract: The interactions between flavors (hexyl acetate [HxAc], heptyl acetate [HpAc], linalyl formate [LiFo], linalyl acetate [LiAc], geraniol, linalool, limonene and myrcene) and soy protein isolate (SPI) were investigated, the influence of flavors structure and preheated SPI (PSPI) were determined by using headspace solid-phase microextraction gas chromatography–mass spectrometry (HS–SPME/GC–MS) technology. For HxAc and HpAc, the binding of SPI and the flavors decreased in the order nature > 80 °C > 90 °C > 100 °C PSPI, for LiFo, LiAc, geraniol, and linalool, nature < 80 °C < 90 °C < 100 °C PSPI. For limonene and myrcene, an increase in headspace concentration or "salting out" effect was noticed. The NSPI (nature SPI) and PSPI of 80 °C showed two class binding sites for HxAc and HpAc. These results serve as a foundation for further investigation into the effect of preheating of SPI on its ability to bind to flavor-inducing compounds.